Video compression systems - Bock, Alois (London, United Kingdom The Institution of Engineering and Technology, 2009)
The following topics are dealt with: digital video; picture quality assessment; MPEG video compression; non-MPEG video compression; motion estimation; high definition television (HDTV); compression for mobile devices; MPEG decoders; statistical multiplexing; concatenation; transcoding and bit-stream processing.
Electronic reproduction.
Keywords: Video compression; Data compression (Telecommunication).; High definition television; Image analysis; Motion perception (Vision).; Multiplexing; Electronic books